What Are the Factors That Are Preferred by the Visitors in Khulna Region When They Getting Service from the Hotel Industry? - Rafiul, Md. Rafiul Islam (Archives of Business Research, 2022)
The paper is done to identify the factors that are acceptable by the customer in hotel industry of Khulna. Khulna is a central point for tourism and business hub for the southern part of Bangladesh. For the construction of Padma bridge the need of also, increased in this area of Bangladesh. The hotel industry has to work on their ways to get the customer satisfaction. There are many hotels in Khulna that play a special role in the hospitality & tourism industry. The objective of the study is to identify the preferred factors of visitors, to identify the factors that they are not happy actually and to give some suggestions based on the findings that will help the hotel industry to gain the best output from the visitors of Khulna. To satisfy the aim of this report data are collected from fifty four visitors through the questionnaire and analyzed it by using some statistical tools. In this research some factors are found that are preferred by the visitors; hotel staffs are friendly, hotel response is good on request, hotel are clean upon arrival, hotel’s restaurant food quality is good ect. Some negative factors are identified in this research also; recreation facilities are not up to the mark and hotel’s room was not well equipped. The recommendations in that case are to improve the recreational facilities and try to make the room well equipped that will help to get the maximum attractions.